Validity of legal norms with special reference to Kelsen's general theory of law - Pajić-Šavija Sandra (Trendovi u Poslovanju)
The term validity of legal norms usually means the obligation of legal norms for entities whose behavior is regulated by a legal norm. In legal theory, the concept of validity of law is used in a different sense. Kelzen's idea of the validity of law stems from his so-called gradation theory according to which each legal norm is valid on the basis of an immediately higher legal norm, while at the head of the hierarchy is the constitution as the highest legal norm, which bases its validity on the assumed norm. According to Kelzen, a legal norm derives its validity, that is, its obligation, not from its content but from its form. In this sense, legal norms are valid because they are ideally obligatory, regardless of the fact whether subjects are familiar with them and their content. Kelzen puts special emphasis on distinguishing the validity of law from the efficacy of law. While the validity of law means that legal norms are mandatory, that is, that subjects should behave in the manner described in the norm itself, the effectiveness of law means that the addressees actually behave in the manner prescribed by the legal norm. However, although Kelsen separates the validity and effectiveness of a legal norm, he still believes that there is a connection between validity and effectiveness because only an effective norm is considered valid.